Pengaruh Ketersediaan Bunga Jantan Anthesis terhadap Populasi Kumbang Elaeidobius Kamerunicus dan Dampaknya terhadap Penurunan Jumlah Tandan Parthenocarpy - Sinaga, Toni Athory; Astuti, Yohana Th. Maria; Budiharjo, Kadarwati; Afiantoro, Febri; Yusup Paisol (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
Successful pollination in oil palm depends heavily on the availability of Elaeidobius kamerunicus pollinator insects that require anthesis male flowers as habitat and food sources. This study aimed to analyze the relationship between anthesis male flower availability on E. kamerunicus beetle population and its impact on parthenocarpy bunch formation at PT. Graha Inti Jaya, Central Kalimantan. Observational method with descriptive and correlational approaches was conducted on 484.57 hectares of oil palm plants varieties Socfindo and Lonsum planted in 2007-2008 during February-July 2025 period. Data collection included anthesis male flower census, beetle population monitoring using yellow traps, and parthenocarpy bunch analysis from mill sorting. Data analysis used linear regression, Pearson correlation, and two-way ANOVA with 95% confidence level. Results showed significant relationship between anthesis male flower availability and E. kamerunicus beetle population (R² = 0.728, p < 0.05), where each unit increase of anthesis male flower increased beetle population by 2,667 individuals per hectare. However, relationship between beetle population and parthenocarpy bunches was not significant (R² = 0.114, p > 0.05), indicating complexity of pollination factors. Variety and planting year differences showed no significant effect. This study recommends maintaining anthesis male flower availability >5% per hectare for optimal natural pollinator beetle population.